DOI: 10.31274/rtd-180813-10983
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of organic contaminants in water

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Among the advanced oxidation processes used in water and wastewater treatment, photocatalysis, as a green chemical pathway, plays an important role as it is capable of degrading and mineralizing contaminants such as dyes, phenols and pesticides into harmless products under mild conditions (Ike et al 2002;Oh 2004;Wang et al 2009;De la Fuente et al 2010;Ameta et al 2012;Rammohan and Nadagouda 2013;Umar and Aziz 2013;Pirilä et al 2015;Liang et al 2020). This process involves chemical reactions that take place in the presence of light and a photocatalyst.…”
Section: Photocatalyst Nanoparticles For the Degradation Of Alkylphen...mentioning
confidence: 99%
“…Among the advanced oxidation processes used in water and wastewater treatment, photocatalysis, as a green chemical pathway, plays an important role as it is capable of degrading and mineralizing contaminants such as dyes, phenols and pesticides into harmless products under mild conditions (Ike et al 2002;Oh 2004;Wang et al 2009;De la Fuente et al 2010;Ameta et al 2012;Rammohan and Nadagouda 2013;Umar and Aziz 2013;Pirilä et al 2015;Liang et al 2020). This process involves chemical reactions that take place in the presence of light and a photocatalyst.…”
Section: Photocatalyst Nanoparticles For the Degradation Of Alkylphen...mentioning
confidence: 99%
“…It has been suggested that preliminary adsorption is a prerequisite for highly efficient photocatalytic. Because recombination of the photogenerated electron and hole is so rapid, interfacial electron transfer is kinetically competitive only when the relevant donor or acceptor is preadsorbed before photolysis [28]. This process was followed for a time of 90 min with the experimental conditions: [MG] = 5x10 -5 g/mol, V = 110 ml and the measured spectra are represented in Fig.…”
Section: 𝛼 ℎ𝜈 = 𝐴 √ ℎ𝜈 − 𝐸 𝑔mentioning
confidence: 99%